Safety and Impact of Low-dose Methotrexate on Endothelial Function and Inflammation in Individuals With Treated Human Immunodeficiency Virus: AIDS Clinical Trials Group Study A5314. (14th September 2018) - Hsue, Priscilla Y; Ribaudo, Heather J; Deeks, Steven G; Bell, Tanvir; Ridker, Paul M; Fichtenbaum, Carl; Daar, Eric S; Havlir, Diane; Yeh, Eunice; Tawakol, Ahmed; Lederman, Michael; Currier, Judith S; et al.
Abstract: Background: Chronic inflammation in treated HIV infection is associated with mortality and atherosclerotic cardiovascular disease (ASCVD). We evaluated the safety and potential efficacy of low-dose methotrexate (LDMTX) in treated HIV. Methods: This was a phase 2 randomized, double-blind, multicenter trial in adults ≥40 years old with treated HIV, with CD4+ T-cell count ≥400 cells/μL and with/at increased risk for ASCVD. Participants received LDMTX (5–15 mg/week) or placebo (plus folic acid) for 24 weeks and were followed for an additional 12 weeks. Primary endpoints were safety and brachial artery flow-mediated dilation (FMD). Results: The 176 participants (90% male) had a median (Q1, Q3) age of 54 (49, 59) years. LDMTX was associated with decreases in CD4+ T cells at week 24 and CD8+ T cells at weeks 8, 12, and 24. Eleven participants (12.8%) experienced safety events in the LDMTX group vs 5 (5.6%) in placebo (Δ = 7.2%, upper 1-sided 90% CI, 13.4%; Pnoninferiority = .037). Week 24 change in FMD was 0.47% with LDMTX and 0.09% with placebo (P = .55). No inflammatory markers changed differentially with LDMTX compared to placebo. Conclusions: Adults with HIV and increased ASCVD risk treated with LDMTX had more safety events than with placebo, but the prespecified noninferiority margin of 15% was not exceeded. LDMTX had no significant effect on endothelial function or inflammatory biomarkers but was associated with a significant decrease in CD8+ T cells. The balance of risks and potential benefits of LDMTX in this population will require additional investigation. Clinical Trials Registration: NCT01949116. Abstract : Chronic inflammation in treated HIV infection is associated with mortality and atherosclerotic cardiovascular disease. We conducted a phase 2 randomized, double-blind, multicenter trial to evaluate the safety and efficacy of low-dose methotrexate in treated HIV infection.